2020
DOI: 10.1177/0021909620970567
|View full text |Cite
|
Sign up to set email alerts
|

Doing Boundary Work: Suburban Residents’ Associations in Johannesburg

Abstract: Despite best hopes of social and urban transformation, Johannesburg’s middle-class suburbs have remained largely inaccessible to lower income and more marginalised communities. This article examines the everyday practices and repertoires of action by resident associations in Johannesburg, demonstrating their ability to moderate more progressive state impulses and other land use changes. It argues that resident associations have become the custodians of middle-class visions and aesthetics and carry out the boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The analysis uses interview quotes to validate residents' "deep local knowledge" (Streule et al, 2020) about the production of their homes, neighborhoods, and livelihoods. Residents' repertoire of action (Rubin, 2021) simultaneously draws from and reinforces incrementality and affordability, contributing to feelings of appropriation and emplacement, as Streule et al (2020) and Caldeira (2017) have also observed.…”
Section: Residents' and Builders' Experience With Self-buildingmentioning
confidence: 82%
See 1 more Smart Citation
“…The analysis uses interview quotes to validate residents' "deep local knowledge" (Streule et al, 2020) about the production of their homes, neighborhoods, and livelihoods. Residents' repertoire of action (Rubin, 2021) simultaneously draws from and reinforces incrementality and affordability, contributing to feelings of appropriation and emplacement, as Streule et al (2020) and Caldeira (2017) have also observed.…”
Section: Residents' and Builders' Experience With Self-buildingmentioning
confidence: 82%
“…The association between homeownership aspirations, displacement, and "tensions brought about by powerful actors whose interests are poorly mediated through contemporary governance" (Huchzermeyer, 2021, p. 193) is not uncommon in analyses of self-built housing, particularly in the African context. As a response to the disjuncture (Croese et al, 2016) represented by profitseeking actions of powerful state and private actors on the one hand, and the needs, demands, and repertoires (Rubin, 2021) of local communities, on the other hand, critical housing studies have focused on home building and dwelling as lived experience. While the notion of home in these analyses is "complex and multi-scaled, directly tied to human well-being" (Huchzermeyer, 2021, p. 193), a crucial concern is with the loss of home for a variety of factors that can ultimately lead to conditions of "un-homing.''…”
Section: Meanings Of Home and Homeownershipmentioning
confidence: 99%
“…In Kenya, most grassroots organisations in informal settlements take the form of community-based organisations and self-help groups, increasingly organised under the umbrella of resident associations (RAs). Since colonial times, RAs have been the associative form representing residents’ views in middle-class neighbourhoods, responding to government ineptitude in meeting the infrastructural needs of residents (Rubin, 2021). More recently, RAs have increasingly extended to both high- and low-income settlements in Kenya (Echessa, 2010) and other African cities.…”
Section: Organisational and Urban Incompletenessmentioning
confidence: 99%